Resiliensi Guru PAI Sebagai Fasilitator dalam Projek Penguatan Profil Pelajar Pancasila di SMP NU Baitussalam Simbar Cluring Banyuwangi - Fatah, Abdul; Syahid, Mar; Habibah, Nur Faiz (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
This study aims to reveal the form of resilience possessed by Islamic Religious Education (PAI) teachers in carrying out their role as facilitators in the Pancasila Student Profile Strengthening Project at SMP NU Baitussalam Simbar Cluring Banyuwangi. In this study the author used a qualitative research method, with steps used such as using a case study approach, taking data sources from clear informants, data collection techniques. The results are: First, that resilience to the p5 activities is also very much needed because it can raise the teacher's mentality and build children's motivation to care about the environment. Second, that the form of teacher resilience using various dimensions is very necessary for teachers to use in dealing with their problems. Third, with a lack of perseverance, lack of mastery, lack of adequate facilities, limited time, it can be a factor inhibiting the resilience of PAI teachers.